Evaluating impacts of cross-border transport infrastructure in the Greater Mekong Subregion: Three approaches - Manabu Fujimura (Asian Development Bank Institute (ADBI), 2017)
This paper presents three approaches to the evaluation of cross-border transport infrastructure in the Greater Mekong Subregion (GMS). First, it estimates benefit-cost ratios for selected segments of economic corridors. The results indicate differing degrees of economic viability among different corridors. Second, it presents a panel data analysis on how economic corridor developments have impacted living standards at subnational level. The results indicate that economic corridors in the GMS as a whole show a positive net economic impact. Third, it presents a gravity model analysis on how economic corridors have affected intra-GMS trade. The results indicate positive effects of the development of economic corridors on intra-GMS trade in intermediate goods, especially for electric machinery. This implies that cross-border transport infrastructure in the GMS has contributed to lower service link costs and facilitated vertical integration across borders in this industry.
Keywords: F14; F15; O18; 330; project evaluation; cross-border infrastructure; regional integration